2006
DOI: 10.1111/j.1365-2249.2006.03172.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of interferon-γ and interleukin 10 genotypes and serum levels with partial clinical remission in type 1 diabetes

Abstract: SummaryWe studied whether serum interferon (IFN)-γ γ γ γ or interleukin (IL)-10 levels and their corresponding functional polymorphic genotypes are associated with partial remission of type 1 diabetes (T1D). A multi-centre study was undertaken in patients with newly diagnosed T1D and matched controls. T1D patients were followed for 3 months and characterized for remission status. Partial clinical remission was defined as a daily insulin dose ≤ ≤ ≤ ≤ 0·38 units/kg/ 24 h with an HbA1c ≤ ≤ ≤ ≤ 7·5%. Thirty-three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
2
22
1
Order By: Relevance
“…In a limited cross-sectional prospective study, we found that higher FoxP3 expression at diagnosis predicted worse glycemic control, but higher mean numbers of IL-10 cells were associated with better future glucose control. Additionally, others reported lower IFN-␥ levels in remitters (12). Together, these data suggest that there may be an immunological component underlying the honeymoon phase, arguing for antigen-specific immunomodulation to curb autoimmunity soon after diagnosis.…”
Section: E the Honeymoon Phase: Do Beta-cellsmentioning
confidence: 77%
“…In a limited cross-sectional prospective study, we found that higher FoxP3 expression at diagnosis predicted worse glycemic control, but higher mean numbers of IL-10 cells were associated with better future glucose control. Additionally, others reported lower IFN-␥ levels in remitters (12). Together, these data suggest that there may be an immunological component underlying the honeymoon phase, arguing for antigen-specific immunomodulation to curb autoimmunity soon after diagnosis.…”
Section: E the Honeymoon Phase: Do Beta-cellsmentioning
confidence: 77%
“…Yet, even although the distribution of the genetic variants was equal among the progression groups, rapidly progressing patients had significantly higher levels of IFNc compared with other progression groups. Conversely, we have previously shown that patients in clinical remission, defined by HbA 1c £ 58 mmol ⁄ -mol (7.5%) and insulin requirement £ 0.38 U kg -1 day -1 , had significantly lower IFNc levels than patients not in remission, in spite of the presence of IFNc genotypes associated with high IFNc production [14]. IFNc has been described as a key molecule in b-cell destruction [7].…”
Section: Il-10 Genotypesmentioning
confidence: 99%
“…, while there were no associations with either IL-10 levels or genotype frequencies [14]. In this study, we tested the hypothesis that IL-10 and IFNc serum levels in combination with their respective genotypes are associated with disease progression in paediatric patients with newly diagnosed Type 1 diabetes.…”
Section: Introductionmentioning
confidence: 97%
“…We treated islets with a combination of IFN-␥ and IL-1␤ or TNF-␣ and IL-1␤, which are reported to cause islet apoptosis in type 1 diabetes (14,15). The islets were harvested 2, 6, and 24 h after the cytokine stimulation.…”
Section: Rapid Induction Of Drak2 Expression In Islet ␤ Cellsmentioning
confidence: 99%